The Development Strategy of Local Competitive by Metal Industrial - Sasana, Hadi; Atmanti, Hastarini Dwi; Muid, Dul (JEJAK: Jurnal Ekonomi dan Kebijakan, 2018)
In the era of globalized demands readiness state or area to be able to compete. This study dug condition flagship cluster in Central Java that is industrial metal casting in Klaten Regency. Methods of analysis using qualitative and quantitative analysis (R/C Ratio; Analytical Hierarcy Process). Using primary data as well as secondary data collected from selected samples or related institutions. Those results found: (1) the actors cast metal Small medium enterprises (SME) efforts largely have joined in a group/cluster (2). Based on the analysis of the feasibility of the effort, all the effort in the area of the cluster of decent run because it has a value of R/C ratio is more than 1 (one) (3). Industrial cluster development priority scale cast metal are: marketing, production aspects, aspects of the infrastructure, institutional aspects, and managerial aspects.